The use of B-Lynch Technique and Lasso-Budiman Technique to Control Postpartum Hemorrhage in Uterine Atony - Muhammad Nurhadi Rahman (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To evaluate the use of B-Lynch Technique and Lasso Budiman Technique as conservative way to control post partum hemorrhage due to uterine atony. Method: The cross-sectional retrospective study in Department of Obstetrics and Gynecology, Tangerang General Hospital, Banten, year 2005 - 2008 and Department of Obstetrics and Gynecology, Wonosobo General Hospital, Central Java, year 2003 - 2008. Results: Total 38 post partum hemorrhage cases managed conservatively using B-Lynch technique and Lasso-Budiman technique. Twenty-six cases were done at Wonosobo General Hospital using B-Lynch technique, with 1 failure case and hysterectomy was done with good result. No complications has been reported for the rest 25 successful cases. Twelve cases were done at Tangerang General Hospital, using Lasso-Budiman technique, 1 failure reported, continue to hysterectomy. Among 11 successful cases, 2 complications were found. Ssecondary amenorrhea after performing Lasso-Budiman technique due to uterine sinechia were reported. Conclusion: The B-Lynch technique and Lasso-Budiman technique, both are simple, easy, and effective to control post partum hemorrhage due to uterine atony. If failed, hysterectomy is the last choice. These techniques are also effective methods to conserve uterus and fertility. [Indones J Obstet Gynecol 2010; 34-4: 195-8] Keywords: postpartum hemorrhage, conservative methode, BLynch technique, Lasso-Budiman technique